PEMAKNAAN DESAIN KARAKTER SOSOK IBU PADA AKUN INSTAGRAM “PARENTING IS EASY” BAGI IBU MUDA - Palupi Argani; Riama Maslan Sihombing (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
This study aims to discover how the construction of meaning is formed in young mothers regarding theappearance of the character design of the mother figure on the Instagram account Parenting is Easy. The urgencyof this research relates to the phenomenon of using Instagram and the design of the character of the motherfigure as a media for parenting education. This phenomenon will affect the meaning of young mothers in thecharacter design of the mother figure, which beginsto shift due to technological factors and different generations.The meaning of young mothers in the character design of the mother figure will also affect the identity andparenting pattern formed. This study uses a qualitative approach with phenomenological methods. Theconclusion of this study obtained the construction of meaning formed in the design of the character of the motherfigure. These meanings are categorized into two groups: the emotional young mother category and the trendyyoung mother category, which also construct the meaning of two different parenting patterns.